STRATEGI MENCARI MAKAN BURUNG PECUK PADI HITAM (PHALACROCORAX SULDROSTRIS) DI SUAKA MARGASATWA PULAU RAMBUT, TELUK JAKARTA - FlTHRI, AlDA (Jurnal Biologi Udayana, 2008)
Little black cormorant (Phalacrocorax suldrostris} feeding activity around their breeding area face many problem such as high velocity wind and piracy by frigate birds. P. suldrostris developed six type of flying to overcome high velocity wind and flew in group to avoid frigate attack. As much as 13 fish species were consumed by little black cormorant during this research.
Keywords: Food; Phalacrocorax suldrostris; Fregata sp; flight Strategy; flight flock